Organization and execution of sports events: from idea to implementation - Razumna, N. V.; Poliakova, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
This study explores the key elements of sports event management, emphasizing the importance of meticulous planning, coordination, and execution. It examines the various stages involved in organizing a successful event, including budget preparation, venue management, safety protocols, and effective promotional strategies. The research highlights the impact of advertising, social media, and online platforms in attracting participants and spectators. The study concludes that thorough planning, along with well-executed opening and closing ceremonies, significantly contributes to the overall success and long-term impact of sports events, fostering community engagement and promoting active lifestyles.
Keywords: organization; sports events; implementation; idea; planning; event management; promotional activities; logistics; sports facilities; promotion; evaluation